Transformasi Umkm Era Digital: Pelatihan Pemasaran Digital Umkm Lokal Desa Danger Kecamatan Masbagik - Abdul Khalik; Mohamad Ariansidi; Candra .; Risqia Thufhil Laeli; Agung Gunawan Caryadi; Rindiani .; Moh. Gozali (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The community service activity aims to enhance the capabilities of Micro, Small, and Medium Enterprises (MSMEs) in Danger Village, Masbagik District, in utilizing digital marketing strategies to improve their competitiveness amid the evolving digital era. However, the low level of digital literacy and the limited ability of MSME actors to leverage online marketing platforms have constrained local products from reaching wider markets. Therefore, this program provides comprehensive digital marketing training, including an introduction to digital marketing, the use of social media, marketing content creation, and product branding implementation. This initiative is intended to equip MSME actors with practical skills to develop more effective marketing strategies. The implementation method involves interactive lectures, demonstrations, and hands-on practice to ensure optimal learning outcomes. The results of the activity indicate an improvement in participants’ understanding of digital marketing concepts, their ability to create promotional content, and increased confidence in utilizing digital media for product promotion. Furthermore, the training also fosters the development of a digital-based MSME ecosystem in Danger Village as a foundation for strengthening the local economy. This activity is expected to serve as a starting point for supporting the sustainability of digital transformation among MSMEs and to encourage stronger collaboration between village authorities, business actors, and educational institutions in promoting community-based economic development at the village level.